Do Smart Parents Raise Smart Children? The Intergenerational Transmission of Cognitive Abilities - Silke Anger; Guido Heineck (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Complementing prior research on income mobility and educational transmission, we provide evidence on the intergenerational transmission of cognitive abilities using data from the German Socio-Economic Panel Study. Our estimates suggest that individuals' cognitive skills are positively related to the abilities of their parents, even when educational attainment and family background is controlled for. We differentiate between mothers' and fathers' IQ transmission and find different effects on the cognition of sons and daughters. We show that cognitive skills which are based on past learning are more strongly transmitted from parents to children than cognitive skills which are related to innate abilities. Our findings are not compatible with a pure genetic model, but rather point to the importance of parental investments for the cognitive outcomes of children.
Keywords: J10; J24; I20; 330; Cognitive abilities; intergenerational IQ transmission; skill formation